login
The OEIS is supported by the many generous donors to the OEIS Foundation.

 

Logo
Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A241885 Write the coefficient of x^n/n! in the expansion of (x/(exp(x)-1))^(1/2) as f(n)/g(n); sequence gives f(n). 8
1, -1, 1, 1, -3, -19, 79, 275, -2339, -11813, 14217, 95265, -4634445, -193814931, 131301607, 1315505395, -3890947599, -136146236611, 46949081169401, 124889801445461, -10635113572583999, -158812278992229461, 56918172351554857, 8484151253958927197 (list; graph; refs; listen; history; text; internal format)
OFFSET

0,5

COMMENTS

For g(n) see A242225(n).

The old definition was "Numerator of (B_n)^(1/2) in the Cauchy type product (sometimes known as binomial transform) where B_n is the n-th Bernoulli number".

LINKS

Table of n, a(n) for n=0..23.

David Broadhurst, Relations between A241885/A242225, A222411/A222412, and A350194/A350154.

Jitender Singh, On an arithmetic convolution, arXiv:1402.0065 [math.NT], 2014 and J. Int. Seq. 17 (2014) # 14.6.7.

FORMULA

Theorem: A241885(n)/A242225(n) = n!*A222411(n)/(A222412(n)*(-1)^n/(1-2*n)) = n!*A350194(n)/(A350154(n)*(2*n+1)). - David Broadhurst, Apr 23 2022 (see Link).

For any arithmetic function f and a positive integer k>1, define the k-th root of f to be the arithmetic function g such that g*g*...*g(k times)=f and is determined by the following recursive formula:

g(0)= f(0)^{1/m};

g(1)= f(1)/(mg(0)^(m-1));

g(k)= 1/(m g(0)^{m-1})*(f(k)-sum_{k_1+...+k_m=k,k_i<k} k!/( k_1!...k_m!)g(k_1)... g(k_m)), for k>=2.

This formula is applicable for any rational root of an arithmetic function with respect to the Cauchy type product.

E.g.f: sqrt(x/(exp(x)-1)); take numerators. - Peter Luschny, May 08 2014

EXAMPLE

For n=1, B_1=-1/2 and B_1^(1/2)=-1/4 so a(1)=-1.

For n=6, B_6=1/6 and B_6^(1/2)=79/86016 so a(6)=79.

1/1, -1/4, 1/48, 1/64, -3/1280, -19/3072, 79/86016, 275/49152, -2339/2949120, -11813/1310720, 14217/11534336 = A241885 / A242225

MAPLE

g := proc(f, n) option remember; local g0, m; g0 := sqrt(f(0));

if n=0 then g0 else if n=1 then 0 else add(binomial(n, m)*g(f, m)*g(f, n-m), m=1..n-1) fi; (f(n)-%)/(2*g0) fi end:

a := n -> numer(g(bernoulli, n));

seq(a(n), n=0..23); # Peter Luschny, May 07 2014

MATHEMATICA

a := 1

g[0] := Sqrt[f[0]]

f[k_] := BernoulliB[k]

g[1] := f[1]/(2 g[0]^1);

g[k_] := (f[k] -

Sum[Binomial[k, m] g[m] g[k - m], {m, 1, k - 1}])/(2 g[0])

Table[Factor[g[k]], {k, 0, 15}] // TableForm

CROSSREFS

Cf. A242225, A126156, A242233.

Cf. also A222411/A222412, A350194/A350154.

Sequence in context: A027175 A093734 A099421 * A061171 A293561 A240286

Adjacent sequences: A241882 A241883 A241884 * A241886 A241887 A241888

KEYWORD

sign,frac

AUTHOR

Jitender Singh, May 01 2014

EXTENSIONS

Simpler definition from N. J. A. Sloane, Apr 24 2022 at the suggestion of David Broadhurst.

STATUS

approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified February 5 18:47 EST 2023. Contains 360087 sequences. (Running on oeis4.)